Modulation of Autoimmune and Autoinflammatory Diseases by Gasdermins - Liang, Fang; Qin, Weixiao; Zeng, Yilan; Wang, Dan (Frontiers in Immunology, 2022)
Autoimmune diseases and autoinflammatory diseases are two types of the immune system disorders. Pyroptosis, a highly inflammatory cell death, plays an important role in diseases of immune system. The gasdermins belong to a pore-forming protein gene family which are mainly expressed in immune cells, gastrointestinal tract, and skin. Gasdermins are regarded as an executor of pyroptosis and have been shown to possess various cellular functions and pathological effects such as pro-inflammatory, immune activation, mediation of tumor, etc. Except for infectious diseases, the vital role of gasdermins in autoimmune diseases, autoinflammatory diseases, and immune-related neoplastic diseases has been proved recently. Therefore, gasdermins have been served as a potential therapeutic target for immune disordered diseases. The review summarizes the basic molecular structure and biological function of gasdermins, mainly discusses their role in autoimmune and autoinflammatory diseases, and highlights the recent research on gasdermin family inhibitors so as to provide potential therapeutic prospects.